ANALISIS PENGARUH MEDIA SOSIAL, KUALITAS PRODUK DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA ONLINE SHOP ALLFASHION KOTA WAINGAPU) - Nina , Rambu Kudu; Situmorang, Tumpal P (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of this study is to explore the influence of social media, product quality and trust on consumer shopping decisions at Allfashion online shop. The research method uses non-probality sampling with purposive sampling techniques, the sampling criteria are consumers who have made purchases at allfashion online shops at least 2 times and are domiciled in Waingapu City District. Data analysis using multiple regression, the results showed social media, product quality and trust had a significant effect on purchasing decisions.